2010
DOI: 10.1002/etc.178
|View full text |Cite
|
Sign up to set email alerts
|

Stress response of heavy metal mixture present in wastewater and leachate on heat‐shock protein 47‐transfected cells

Abstract: Heavy metals present in water environment and hazardous sites as single compounds or mixture may drastically affect human health. In the present work, we investigated the risk assessment of wastewater effluents and leachate with a focus on three heavy metals-nickel (Ni), cadmium (Cd), and lead (Pb)-and their combined effect on mammalian cells, using Chinese hamster ovary cells transfected with the heat-shock protein (HSP) 47 promoter. The heavy metal mixture model was designed based on the concentrations of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Nevertheless, higher concentrations above 1% caused a cytotoxic effect even significant at 20% concentration. The stress response induced by the TWW samples might be related to the Cd content (Table 1) combined to a mixture of heavy metals responsible of a significant stress response in accordance with our recent works [10].…”
Section: Stress Response Effect Of the Wastewater Effluent And The Sosupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, higher concentrations above 1% caused a cytotoxic effect even significant at 20% concentration. The stress response induced by the TWW samples might be related to the Cd content (Table 1) combined to a mixture of heavy metals responsible of a significant stress response in accordance with our recent works [10].…”
Section: Stress Response Effect Of the Wastewater Effluent And The Sosupporting
confidence: 90%
“…Moreover, the pH values for the irrigated soil vary between 7.82 and 8.17. The highest values, which could favor metal binding to biomass [10], are localized in depth. Overall, the heavy metal levels in the irrigated soil were higher than the control soil (C10 and C40) due to the prolonged irrigation (20 years).…”
Section: Water Quality Parameters and Heavy Metal Levelsmentioning
confidence: 99%
“…This increase in the stress response is likely to be associated with the release of bacterial by-products (LPS endotoxin) as reported by Guizani et al 2009 [26]. Ben Fredj et al 95 2010 [31] reported that, in certain conditions, presence of organic matter (bacterial by-products in this case) masks the heavy metal effect.…”
Section: Resultsmentioning
confidence: 74%
“…Nickel, lead, and cadmium were three heavy metals found in wastewater effluents collected in Tunisia (Ben Fredj et al, 2010). If not removed from the treated effluent stream prior to being discharged into the environment, the mixture of the heavy metals had very damaging health effects.…”
Section: Non-potable Reusementioning
confidence: 99%